Cernunnos/Xlf Deficiency Results in Suboptimal V(D)J Recombination and Impaired Lymphoid Development in Mice - Roch, Benoit; Abramowski, Vincent; Chaumeil, Julie; de Villartay, Jean-Pierre (Frontiers in Immunology, 2019)
Xlf/Cernunnos is unique among the core factors of the non-homologous end joining (NHEJ) DNA double strand breaks (DSBs) repair pathway, in the sense that it is not essential for V(D)J recombination in vivo and in vitro. Unlike other NHEJ deficient mice showing a SCID phenotype, Xlf-/- mice present a unique immune phenotype with a moderate B- and T-cell lymphopenia, a decreased cellularity in the thymus, and a characteristic TCRα repertoire bias associated with the P53-dependant apoptosis of CD4+CD8+ DP thymocytes. Here, we thoroughly analyzed Xlf-/- mice immune phenotype and showed that it is specifically related to the DP stage but independent of the MHC-driven antigen presentation and T-cell activation during positive selection. Instead, we show that V(D)J recombination is subefficient in Xlf-/- mice in vivo, exemplified by the presence of unrepaired DSBs in the thymus. This results in a moderate developmental delay of both B- and T-lymphocytes at key V(D)J recombination dependent stages. Furthermore, subefficient V(D)J recombination waves are accumulating during Tcra rearrangement, causing the typical TCRα repertoire bias with loss of distal Vα and Jα rearrangements.